2001
DOI: 10.1177/0022002701045002002
|View full text |Cite
|
Sign up to set email alerts
|

Adjudication without Enforcement in GATT Disputes

Abstract: Disputes under the General Agreement on Tariffs and Trade (GATT) exhibit a puzzling selection effect. Defendants concede more prior to GATT judgments than afterward, despite GATT's lack of enforcement power. Yet, why would states plea-bargain if they know they can spurn contrary rulings? To find out, the article develops an incomplete information model of trade bargaining with the option of adjudication. The plaintiff has greater resolve prior to a ruling, believing that the defendant might be compelled to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 12 publications
1
68
0
3
Order By: Relevance
“…The handful of cross-national analyses have focused primarily on the duration of the negotiation process itself (Michalopoulos 2002;Evenett and Primo Braga 2005;Yu and Wong 2008) or analyzed post-colonial states' economic patterns with a different theoretical focus, treating GATT/WTO membership only as a control variable rather than the question of interest (Head et al 2010). Rather than focusing on the timing of accession, scholars of international political economy have devoted the bulk of their efforts to measuring the effects of institutional membership on trade flows and national trade policies (Gowa and Kim 2005;Rose 2004;Goldstein et al 2007;Subramanian and Wei 2007), to clarifying the dynamics of trade round negotiations (Baldwin 2007;Jones 2009a, b;Odell 2009), and to explaining variation in the escalation, outcome, and effects of trade disputes (Busch 2000;Busch and Reinhardt 2001Reinhardt 2001;Guzman and Simmons 2002;Allee and Huth 2006;Kim 2008;Sattler and Bernauer 2008;Davis and Blodgett Bermeo 2009). Previous work has also explored the relationship of developing countries to the GATT/WTO (Pietras 1998;Finger and Winters 1998;Drahos 2003;Clapp 2006;Davis 2006;Patel 2008), as well as the potential for forum shopping in the settlement of trade disputes created by the overlapping jurisdictions of the GATT/WTO and preferential trade agreements (PTAs) (Davis 2006;Busch 2007;Naoi 2009).…”
Section: The Political Economy Of Gatt/wto Accessionmentioning
confidence: 99%
“…The handful of cross-national analyses have focused primarily on the duration of the negotiation process itself (Michalopoulos 2002;Evenett and Primo Braga 2005;Yu and Wong 2008) or analyzed post-colonial states' economic patterns with a different theoretical focus, treating GATT/WTO membership only as a control variable rather than the question of interest (Head et al 2010). Rather than focusing on the timing of accession, scholars of international political economy have devoted the bulk of their efforts to measuring the effects of institutional membership on trade flows and national trade policies (Gowa and Kim 2005;Rose 2004;Goldstein et al 2007;Subramanian and Wei 2007), to clarifying the dynamics of trade round negotiations (Baldwin 2007;Jones 2009a, b;Odell 2009), and to explaining variation in the escalation, outcome, and effects of trade disputes (Busch 2000;Busch and Reinhardt 2001Reinhardt 2001;Guzman and Simmons 2002;Allee and Huth 2006;Kim 2008;Sattler and Bernauer 2008;Davis and Blodgett Bermeo 2009). Previous work has also explored the relationship of developing countries to the GATT/WTO (Pietras 1998;Finger and Winters 1998;Drahos 2003;Clapp 2006;Davis 2006;Patel 2008), as well as the potential for forum shopping in the settlement of trade disputes created by the overlapping jurisdictions of the GATT/WTO and preferential trade agreements (PTAs) (Davis 2006;Busch 2007;Naoi 2009).…”
Section: The Political Economy Of Gatt/wto Accessionmentioning
confidence: 99%
“…Meanwhile, an even larger literature was growing that studied all aspects of policy making in the European Union with an increasing degree of empirical and theoretical sophistication Schneider 2009;Thompson et al 2006). Simultaneously, a sophisticated empirical literature has emerged that studies dispute resolution in the WTO, the emergence of preferential trade agreements and the proliferation of bilateral investment treaties (Reinhardt 2001;Steinberg 2002;Davis 2003Davis , 2004Davis , 2012Busch and Reinhardt 2003;Mansfield and Reinhardt 2003;Büthe and Milner 2008;Mansfield and Milner 2012). Along the way, a number of anomalies have emerged that challenge the paradigm of explaining outcomes in terms of formal-legal treaty provisions, and scholars working in diverse areas have converged on an appreciation of the significance of informal governance in international organizations.…”
mentioning
confidence: 99%
“…The dispute settlement system forms the central mechanism to enforce international trade law and embodies a high level of legalization in comparison with other international institutions. It has attracted wide attention from scholars in political science, economics, and law (e.g., Bagwell and Staiger 1999;Bown 2004b;Busch 2000;Guzman and Simmons 2002;Jackson 1997;Maggi 1999;Reinhardt 2001;Rosendorff 2005). While research has found no evidence of any bias in rulings against developing countries (Busch and Reinhardt 2003;Moon 2006), weak enforcement could arise through an earlier selection effect if developing countries do not file complaints to challenge violations.…”
mentioning
confidence: 99%